Use of Chloral Hydrate as a Sedative Agent before General Anesthesia in Pediatric Population Undergoing Eye Examination - Mehdi Sanatkar; Fariba Ghassemi; Alireza Khodabande; Hossein Sadrossadat; Ebrahim Espahbodi; Mehrdad Shoroughi; Alireza Ebrahim Soltani; Jalil Makarem; Mehrdad Goudarzi; Amir Abbas Yaghooti; Mihan Jafari Javid; Anahid Maleki (Archives of Anesthesia and Critical Care, 2015)
Background: Chloral hydrate (CH) is a sedative agent that is widely used in infants and children for several decades. The purpose of this study was to evaluate the safety and efficacy of CH before general anesthesia in pediatric population undergoing eye examination. Methods: 165 pediatric patients with retinal tumor were examined from December 2014 to May 2015. 158 (95.7%) children were sedated by CH before general anesthesia. CH was used at a dose of 25 mg/kg with an augmentation dose, if necessary, in 20-30 minutes. We recorded the safety of CH, the success or fail of sedation, augmentation CH dose, time to sedation and complications of CH administration. Results: In our study 158 (95.7%) children were sedated by CH and sixty four (40.5%) of these patients were under one year of age and ninety four (59.5%) were older. Successful sedation was achieved in 150/158 (94.9%) of the children. The success rate of sedation was higher in children below 1 year of age (63/64; 98.4%) compared to subjects older than 1 year (88/94; 93.6%) (P=0.01). The mean of time to sedation was 20.8±12.4 and 22.4±14.8 minutes in children below 1 year of age and older than 1 year respectively (p=0.91). Complications were observed in 4/158 (2.5%) of the children. We observed no episodes of desaturation after administration of CH in all subjects. Conclusion: CH is a safe and effective sedative agent for children before general anesthesia provided it is used in a hospital setting with appropriately trained staff.